Automatic Reappraisal-Based Implementation Intention Produces Early and Sustainable Emotion Regulation Effects: Event-Related Potential Evidence - Chen, Shengdong; Yu, Kang; Yang, Jiemin; Yuan, Jiajin (Frontiers in Behavioral Neuroscience, 2020)
Implementation intention has proven effective in regulating intense emotions，however, which is found to be difficult when instructed regulation is used. Here, we aim to test whether automatic reappraisal based implementation intentions (RII) down-regulates intense negative emotion more efficiently than controlled reappraisal (CR) using a two-phase event-related potential (ERP) experiment. In the regulation phase, both RII and CR decreased subjective experiences of negative emotion relative to passive watching, irrespective of emotional intensity. Further, RII reduced the central-parietal late positive potential (LPP) amplitudes for both intensities in the 300-1700ms epoch after picture onset, whereas CR reduced LPP amplitudes just in the 500-700ms interval. Furthermore, the application of RII but not CR produced a reliable long-term LPP attenuation compared to passive watching in the unexpected re-exposure phase. These findings demonstrate that reappraisal based implementation intention yields an earlier and more sustainable emotion regulatory effects than controlled reappraisal.